'I go home with a happy heart'. Enhancing community aged care services to sustain togetherness: Perspectives from Australian staff and clients. (11th October 2021) - Siette, Joyce; Knaggs, Gilbert; Nguyen, Amy D; Brett, Lindsey; Jorgensen, Mikaela; Gow, Edwina; Georgiou, Andrew
Abstract: Social participation is critical to the health and well‐being of older adults, however, participation often declines with age. Research has identified that personal and environmental factors such as high socioeconomic status and accessible transportation are associated with higher levels of social participation. However, the barriers and facilitators to social participation experienced by older adults receiving community aged care services remains largely unexplored. This qualitative study aimed to generate context‐rich data and identify the barriers and facilitators to effective community care services that can support older adults' participation in the community and contribute to individual well‐being. Semi‐structured focus groups were conducted with 40 community aged care clients and 21 staff members between January to July 2018 and thematic analysis was undertaken. Environmental factors, such as availability and accessibility of transportation services emerged as the most important factors influencing participation. Older age, self‐attitude towards one's own functional ability and limited social networks were important personal factors affecting participation. Proactive aged care services (e.g., engaged staff, tailored activities) were reported to assist with continual engagement in aged care services. In contrast, the type, location and accessibility of the activity, associated costs and limited options for accessible transportation were key barriers to older adults' social participation. Pathways contributing to positive engagement were complex and variable, but personal well‐being and local community resources emerged as important factors encouraging higher social participation. These findings are discussed in the context of the ongoing pandemic and implications for future aged care services are provided.